Analysis of Educational Financing Management Based on Management Function: Planning, Budgeting, Accounting, Auditing, and Reporting in Primary Schools - Ananda Vian Saleh Presiden; Nur Irma Fitriani; Eni Arianti; M. Agung Wahyudi; Nurkolis (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze educational financing management based on management functions, including planning, budgeting, accounting, auditing, and reporting, at the primary school level. Effective financial management is essential to ensure transparency, accountability, and optimal utilization of educational resources in supporting school programs. This study employed a qualitative approach with a descriptive research design. The research was conducted at SD Negeri Purwoyoso 04 Semarang in 2026. Data were collected through in-depth interviews, observations, and document analysis involving the principal, school treasurer, and teachers involved in school program management. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results indicate that educational financing management has been implemented systematically through five interconnected functions. The planning function is carried out through participatory preparation of the School Activity and Budget Plan (RKAS). Budgeting is implemented based on school priorities, while accounting is conducted through systematic financial recording. Auditing is performed through internal and external supervision mechanisms, and reporting is conducted periodically as a form of accountability. This study provides a comprehensive perspective on school financing management by integrating five financial management functions into a unified analytical framework. The findings imply that strengthening financial management capacity among school leaders and financial administrators is necessary to improve transparency, accountability, and effectiveness in educational financing.